Wakaf Produktif Sebagai Pengentasan Kemiskinan: Studi Komparasi antara Tafsir Al-Qur’an dan Undang-undang Wakaf di Indonesia - Samheri, Samheri; Sholehah, Mamluatus; Zahrah, Mutimatus (International Conference on Islamic Studies, 2021)
Allah SWT. ordered His servants to spend some of their wealth in terms of goodness, such as waqf, zakat, infaq, sedeqah, hibbah and so on. This study uses qualitative research methods, with the type of library research. While the analysis used is comparative inductive. This research produces findings about the management and development of productive waqf, both from the aspect of Islamic law and legislation. In Law No. 41 of 2004 article 15 states that the meaning of waqf is a legal act of a person or group that separates part of his property to institutionalize it forever for the benefit of worship or other public purposes and in accordance with Islamic teachings. Productive waqf can be used for production purposes, be it from agriculture, industry, trade and services whose benefits are not directly on waqf objects but through net profits from the results of waqf development given to entitled people. And the right steps for productive waqf need to be developed a system of management and development of waqf by sharing models and business management to alleviate poverty and prosper the people, nation and state.